Daily sperm production and evaluation of morphological reproductive parameters of Murrah buffaloes in an extensive breeding system - Luz, Patricia A. C. da [UNESP]; Andrighetto, Cristiana [UNESP]; Santos, Paulo R. S.; Jorge, André Mendes [UNESP]; Constantino, Maria Vitoria P.; Pereira, Flávia T. V. [UNESP]; Mess, Andrea M.; Assis Neto, Antônio Chaves de (Taylor & Francis, 2012)
The development of male sexual maturity varies among buffaloes. The Murrah buffalo is considered the most important and efficient milk and fat producer, but aspects of its reproductive biology are still unknown. The present study aimed to evaluate the daily sperm production (DSP) and spermatogenesis in developing Murrah buffalo bulls by evaluation of the seminiferous tubules, testicular morphometry and using light microscopy and scanning electron microscopy. The testes of Murrah buffalo bulls at 18 mo was immature and at 24 mo could still be considered an average-efficiency breed based on their DSP. At 24 mo, the DSP rate was 0.97 billion sperm per testis and 13 million sperm per gram of testis. However, the animals had superior morphometric parameters compared with those of other livestock animals, except for the seminiferous tubule volume and diameter, which were inferior. In conclusion, our data support former views that the testes of the Murrah breed does not reach sexual maturity before 2 y of age and that important developmental steps occur later than Murrah crossbreeds from Brazil.
Keywords: Buffaloes; Histometry; Sexual development; Sperm production; Testes